2016
DOI: 10.1155/2016/1379289
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations Associated with Overweight/Obesity in Puerto Ricans with Fibromyalgia Syndrome

Abstract: Objective. To determine the clinical manifestations associated with overweight/obesity in Hispanics from Puerto Rico with fibromyalgia syndrome (FMS). Methods. A cross-sectional study was performed in 144 patients with FMS (per American College of Rheumatology (ACR) classification criteria). Sociodemographic features, FMS-related symptoms, tender points (per ACR criteria), comorbidities, and FMS treatment were examined. BMI was calculated and patients were grouped into two categories: BMI ≤ 24.9 kg/m2 (nonover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It was also reported that obese FMS patients had worse depression scores, lower upper body strength, worse disability scores and more use of FMS medications than nonobese counterparts [18,22]. In addition, obese FMS patients were more likely to experience self-reported memory impairment, anxiety, shortness of breath, urinary frequency and higher tender point counts [23].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that obese FMS patients had worse depression scores, lower upper body strength, worse disability scores and more use of FMS medications than nonobese counterparts [18,22]. In addition, obese FMS patients were more likely to experience self-reported memory impairment, anxiety, shortness of breath, urinary frequency and higher tender point counts [23].…”
Section: Discussionmentioning
confidence: 99%